Pesticides: Health impacts and alternatives. Proceedings of a workshop held in Colombo, 24 January 2002 - Smit, L.A.M. (International Water Management Institute, 2002)
The International Water Management Institute (IWMI) has, for many years, been involved in research on pesticide poisoning to analyse the reasons for the high number of pesticide poisoning cases in Sri Lanka and discuss ways of controlling the problem through changes in agricultural practices and community involvement. More recently, research has focused on risk factors for deliberate and occupational pesticide poisoning and on the impact that a shift towards Integrated Pest Management (IPM) will have on the health of farming families. A workshop on ?Pesticides: Health Impacts and Alternatives? was held at the Colombo Hilton Hotel on 24 January 2002. The workshop marked the end of IWMI?s research on pesticide poisoning in Sri Lanka and provided researchers and policy makers from various disciplines such as health, environment, and agriculture an opportunity to share and discuss recent findings and to discuss strategies to reduce pesticide poisoning. This paper presents the workshop proceedings and includes a resource handbook for Sri Lanka on health impacts of pesticides and alternatives by listing names of relevant institutes, addresses and annotated references.